UJI KETAHANAN PENYAKIT MOTILE AEROMONAS SEPTICEMIA (MAS) MENGGUNAKAN BAKTERI Aeromonas hydrophila PADA IKAN PATIN TRIPLOID - Hartami, Prama (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2024)
Motile Aeromonas Hydrophila (MAS) disease caused by Aeromonas hydrophila is a common pathogen that attacks freshwater fish commodities, including triploid as the new strain of striped catfish. The purpose of this study was to test the resistance of triploid catfish to MAS infection before being released to cultivators as a new commodity to increase national striped catfish production. The test was carried out for 2 months at the Sukamandi Fish Breeding Research Institute, Subang by injecting A. hydrophila bacteria into triploid and diploid catfish. The challenge test was carried out by injecting the cultured A. hydrophila bacteria with a density of 107 cfu.mL-1 as much as 0.1 mL.tail-1 at fish intramuscularly in all treatments, while in the Control (-) treatment, 0.1 mL of PBS solution was injected.tail-1. The test striped catfish used for each treatment were 10 tails measuring 9.23 – 9.65 cm, and weighing 7.1 – 9.23 g. Survival parameter data and blood picture were analyzed quantitatively using Microsoft Excel 2010 and SPSS version 16.0 software with analysis of variance (ANOVA) at 95% confidence interval. The results of re-characterization with biochemical tests showed that A. hydrophila bacteria were gram negative, oxidase and catalase positive, motile, could fermentative convert sugar and could grow in blood media. The survival of triploid striped catfish after the test was 95%, total erythrocytes on day 7, and total leukocytes on the first day were significantly different from diploid striped catfish. Thus, it can be concluded that striped triploid catfish are more resistant to infection with A. hydrophila bacteria than diploid.